Differential effects of subchronic Phencyclidine on anxiety in the light-enhanced startle-, light/dark exploration- and open field tests - Enkel, Thomas; Thomas, Mara; Bartsch, Dusan (Behavioural brain research, 2013)
Subchronic treatment with the N-methyl-d-aspartate receptor antagonist phencyclidine (PCP) is a valuable approach to model the symptomatology of schizophrenia, a multi-facetted psychiatric disorder, in rodents. We addressed the question whether subchronic PCP (scPCP) treatment (5mg/kg bidaily for 7 days) would affect anxiety in rats, since contradictory findings have been reported so far. Anxiety-like behaviour was assessed using the light-enhanced startle paradigm (LES), a method which measures the effect of the natural aversion to light on the startle reflex and does not depend on motivated behaviour or exploratory drive. For comparison, anxiety-like behaviour was measured in the light-dark exploration test (LDT) and in an open field environment (OFT). The scPCP-treatment did not affect baseline startle reactivity or light-enhanced startle, suggesting normal anxiety levels in treated animals. Further, normal anxiety-like behaviour was also found in the OFT. In the LDT, scPCP treated rats displayed shorter latencies to enter the lit compartment and shuttled more between the dark and lit compartments, behaviours indicative of decreased anxiety and/or increased exploratory activity. Our findings therefore suggest that the effects of scPCP-treatment on anxiety-like behaviour are task-dependent and recommend the additional use of tests independent from exploratory drive or other motivated behaviours, such as the LES paradigm.
Gesehen am 24.03.2022